2011
DOI: 10.1007/s10717-011-9369-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complex thinning composition based on oxyethylidenediphosphonic acid, liquid glass, and soda on the structural–mechanical properties of a clay suspension

Abstract: The effect of a complex additive based on oxyethylidenediphosphonic acid, soda, and liquid glass on the viscosity and thixotropy of a Stephan Schmidt clay suspension is studied. The full factorial experiment method is used to obtain regression equations describing the dependence of the structural-mechanical properties of the suspension on the composition and quantity of the complex additive. The compositions of the thinning agent which give the lowest possible viscosity and thixotropy are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The viscosity and thixotropy of the clay and kaolin suspensions are taken as the response functions (by analogy to [5,6] for Stephan Schmidt 13250 clay).…”
Section: Casting Slip Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscosity and thixotropy of the clay and kaolin suspensions are taken as the response functions (by analogy to [5,6] for Stephan Schmidt 13250 clay).…”
Section: Casting Slip Preparationmentioning
confidence: 99%
“…In a previous work we proposed a new deflocculent based on oxyethylidenediphosphonic acid (OEDPA, empirical formula C 2 H 8 O 7 P 2 ) in combination with soda and liquid glass [5,6]. It was found that such a ternary system gives a clay suspension with lower viscosity and thixotropy in a wide range of concentrations.…”
mentioning
confidence: 99%